2002
DOI: 10.1080/10420150215761
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for TL dating with zircon: Computer simulation of temperature and dose rate effects

Abstract: Natural zircon is irradiated internally by U and Th impurities. After exposure to ionizing irradiation zircon exhibits thermoluminescence (TL), which can be used to calculate the irradiation dose and the sample age. A kinetic model for TL of zircon developed earlier is used to model the processes relevant for dating. The response of zircon to irradiation at different dose rates is simulated for different temperatures. Several scenarios for the dating procedure are considered, including laboratory added irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Therefore laboratory irradiation at a suitable, elevated temperature might produce approximately the same occupancies of the deep electron and hole traps as under natural irradiation at ambient temperature. This idea together with preliminary calculations has been presented in a recent, short communication [7]. In section 3.3 the emulation of natural irradiation by laboratory irradiation at elevated temperature is discussed in detail-we present an analytical justification, which agrees well with the simulated results.…”
Section: Introductionsupporting
confidence: 56%
“…Therefore laboratory irradiation at a suitable, elevated temperature might produce approximately the same occupancies of the deep electron and hole traps as under natural irradiation at ambient temperature. This idea together with preliminary calculations has been presented in a recent, short communication [7]. In section 3.3 the emulation of natural irradiation by laboratory irradiation at elevated temperature is discussed in detail-we present an analytical justification, which agrees well with the simulated results.…”
Section: Introductionsupporting
confidence: 56%
“…In a short communication[22] we have presented the results of a successful application of kinetic modelling to simulate the processes relevant for dating.…”
mentioning
confidence: 99%
“…This suggests that only the deep traps associated to the broad 420 °C TL peak contribute directly to the Tb 3+ related OSL emission. For stimulation wavelengths of 875nm OSL has been detected only in the 380-390 nm range of the [SiO 4 ] 4-luminescent emission [4]. Pulse annealing experiments have shown that this OSL signal can be thermally bleached at about 400 °C (Fig.…”
Section: -mentioning
confidence: 96%
“…1(a), dotted curve). The treatment is equivalent with the storage in the dark for long periods of time [4]. The OSL decay curves recorded in the 350-450 nm range and at wavelengths 550 and 583 nm using IR light stimulation (above 700 nm) are presented in the Fig.…”
Section: Temperature ( O C)mentioning
confidence: 99%